Islamic Family Law and the Protection of Single Mothers: A Response to the Rising Trend of Divorce - Megasari, Indah Dewi; Setyawan, Setyawan (PT. Anagata Sembagi Education, 2025)
This article examines the normative and institutional gaps in the legal protection of single mothers within Islamic family law, especially in the context of rising divorce rates in Muslim societies. Using a normative-juridical and conceptual approach, the study analyzes classical Islamic legal frameworks, maqāṣid al-sharī‘ah, and national legal instruments in Indonesia. It also draws comparative insights from other Muslim-majority countries to explore how Islamic values can be harmonized with gender-sensitive policy reform. The findings reveal that although Islamic law provides foundational principles for post-divorce responsibilities, its literal application often fails to address the socioeconomic vulnerabilities faced by women. The study argues that a contextual reinterpretation grounded in maqāṣid values such as justice and dignity is both theologically valid and socially necessary. Rather than positioning Islamic law as merely reactive to modern social demands, this study contributes to contemporary Islamic legal scholarship by framing the protection of single mothers as a legitimate evolution of sharī‘ah-based justice. It demonstrates that contextual ijtihād can serve as a methodological bridge between normative doctrine and lived realities, thereby reinforcing the transformative capacity of Islamic law in advancing inclusive legal systems.